Cryopreservation of fish gametes and embryos - DIWAN, A D; AYYAPPAN, S; LAL, K K; LAKRA, W S (The Indian Journal of Animal Sciences, 2010)
Cryopreservation of gametes is one of the important ex situ methods of conservation of germplasm and has wide ranging applications in aquaculture and fisheries management. Though sperm cryopreservation has been a success in fishes, yet developing successful protocols for eggs and embryo cryopreservation still remains elusive. Despite successful sperm cryopreservation protocol known for more than 200 fish species, the adoption of the technique at commercial level for fish seed production has been limited. High degree of variability in the procedural requirements and success not only between the species but at times within the species, is considered one of the limiting factors in its utilization. The present paper records the status of gamete cryopreservation in fish species. The paper provides a comprehensive review of various aspects of milt cryopreservation such as milt collection, sperm quality and viability assessment, extender compositions, cryoprotectants equilibration periods, freezing rates, thawing of cryopreserved milt and fertilization of eggs and ultrastructural studies on damages in cryopreserved spermatozoa. The paper also provides a brief review of cryopreservation of fish embryos and embryonic stem cells.